2011
DOI: 10.1080/00222895.2011.555436
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Effects of Shifting the Focus of Attention in a Simple Force Production Task

Abstract: Research on the focus of attention has begun exploring the physiological changes that underlie the difference between internal and external foci of attention. However, previous electromyography studies have used dynamic tasks, making it difficult to interpret electrophysiological data. The authors analyzed how the focus of attention affects a subject's ability to perform an isometric force production task (focus was directed either at the force platform or the muscles responsible for force production). Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 49 publications
10
85
0
Order By: Relevance
“…Instructional sets that encourage an internal focus of attention are more likely to induce conscious processing strategies resulting in slower and more purposeful movements, increased pre-movement times [26,28], and increased co-contraction of antagonist muscle groups. For example, under instruction to direct attention internally young adults will increase the co-contraction of affecting muscle groups during a biceps curl [29]. In contrast, when attention is directed externally toward action-effects rather than the action itself, the control processes are more likely to be subconscious, less prone to forgetting and more likely to be resistant to external stressors such as anxiety [25,26].…”
Section: Freezing Degrees Of Freedom: a Motor Learning Perspectivementioning
confidence: 97%
“…Instructional sets that encourage an internal focus of attention are more likely to induce conscious processing strategies resulting in slower and more purposeful movements, increased pre-movement times [26,28], and increased co-contraction of antagonist muscle groups. For example, under instruction to direct attention internally young adults will increase the co-contraction of affecting muscle groups during a biceps curl [29]. In contrast, when attention is directed externally toward action-effects rather than the action itself, the control processes are more likely to be subconscious, less prone to forgetting and more likely to be resistant to external stressors such as anxiety [25,26].…”
Section: Freezing Degrees Of Freedom: a Motor Learning Perspectivementioning
confidence: 97%
“…Lohse, Healy, and Sherwood (2011) found fewer co-contractions of agonist and antagonist muscles with an external relative to an internal focus on an isometric force production task, in addition to more accurate force production ( Figure 5) (see also Lohse & Sherwood, 2012). Furthermore, an analysis of the power spectral density of the EMG signal in the Lohse et al (2011) study demonstrated increases in the median power frequency-indicating superfluous motor unit recruitment of larger motor units within the muscles-when participants focused internally.…”
Section: Muscular Activitymentioning
confidence: 99%
“…Finally, Christina and Alpenfels showed that experienced golfers learned to change their swing path more effectively with external rather than internal focus instructions. Overall, it is clear that the performer's attentional focus fundamentally Lohse et al (2011). The task involved pushing against a force platform with the foot and producing 30% of the maximal force.…”
Section: Movement Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is one study proposing generally lower EMG activity when using an EF compared to an IF in CMJs (Wulf et al, 2010), a more recent study indicates comparable activity in the prime movers but reduced activity in the antagonist muscle when performing an isometric force task (Lohse, Sherwood, & Healy, 2011). Although we measured activity in three shank muscles and the VM, we did not assess EMG of hamstring muscles.…”
Section: Electromyographic Datamentioning
confidence: 99%